2021
DOI: 10.1002/ese3.865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the hydrofoil blade on the pressure pulsation and jet‐wake flow in a centrifugal pump

Abstract: A hydrofoil blade design (HBD) is proposed to suppress the unsteady pressure pulsations in a centrifugal pump. Numerical simulation is carried out using the SST k‐ω model to obtain the unsteady flow field in the pump both with HBD and the conventional blade design (CBD). The pressure pulsations with the two types of blade profiles are compared at the nominal flow rate, whereas the jet‐wake flow patterns and vortex structures are analyzed to clarify the effect of the HBD on the flow field. The pressure pulsatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Figure 17 shows the turbulent kinetic energy (TKE) at the diffuser throat at mid‐span; the green lines indicate the suction side of the vane leading edge whereas L is defined as L = φ/360°. Herein, angle φ is introduced 45 . TKE reduces at the vane pressure surface while high values are recorded for stall flow conditions 0.2 Φ Ν .…”
Section: Resultsmentioning
confidence: 99%
“…Figure 17 shows the turbulent kinetic energy (TKE) at the diffuser throat at mid‐span; the green lines indicate the suction side of the vane leading edge whereas L is defined as L = φ/360°. Herein, angle φ is introduced 45 . TKE reduces at the vane pressure surface while high values are recorded for stall flow conditions 0.2 Φ Ν .…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that the influence of different turbulence models on the calculation results is small, and the relative error is lower than 3%, which satisfies the precise requirements of the relevant calculation. In this study, SST k-ω was selected as the turbulent model for subsequent calculation, because it can obtain the wall separation flow and shear flow under the off-design condition well [22][23][24].…”
Section: Simulation Setupmentioning
confidence: 99%
“…The results show that the unsteady radial force gradually decreased with the increase of blade wrap angle. Similarly, as for the blade thickness distribution, Zhang Y [17] found that the impeller blades with the design of airfoil thickness distribution could reduce the jet wake phenomenon at the impeller outlet to a certain extent, thus reducing the pressure pulsation inside the centrifugal pump. Yousefi H [18] and Li X [19] et al studied the influence of the blade load distribution on internal pressure pulsation and radial force for a low specific speed centrifugal pump.…”
Section: Introductionmentioning
confidence: 96%
“…For the dynamic characteristic of the pump, many factors such as the structure of the impeller blade, the design parameters of the volute casing and the intense rotor-stator interaction are closely related to the radial force, which will further result in the vibration and noise during the operation and even lead to the severe fatigue damage. In terms of the impeller parameters, numerous studies have been carried out by changing the blade profile, such as the blade outlet [9][10][11][12][13][14], wrap angle of the blade [15,16], distribution of blade thickness [17][18][19][20], and splitter blades [21,22], to investigate the relationship between the structure parameters with the flow-induced vibrations both numerically and experimentally. In terms of the influence of blade outlet shape, Nishi [9] et al studied the unsteady radial force exerted on the centrifugal pump impeller relating to the blade outlet angle.…”
Section: Introductionmentioning
confidence: 99%